Additions to the orchid flora of Andaman and Nicobar Islands, India - Alappatt, Joju P. (Rheedea, 2016)
Bulbophyllum odoratissimum (Sm.) Lindl. and Dendrobium spatella Rchb.f. (Orchidaceae), so far known from Eastern Himalaya and northeast India are reported here as additions to the flora of Andaman and Nicobar Islands for the first time. Brief descriptions with illustration and photographs are provided for correct identification.